Agricultural Sector Development Strategy Based On Superior Commodities In Encouraging Economic Growth In Central Kalimantan - Bismart Arituan; Zakia Putri Sulaiman (Community Engagement and Emergence Journal (CEEJ), 2026)
The agricultural sector serves as the primary foundation of Central Kalimantan's economy, yet its full potential remains unrealized due to limited downstream processing facilities and persistent inter-regional disparities. This study aims to identify leading agricultural commodities, evaluate their contribution to regional economic growth, and formulate appropriate sustainable development strategies. A qualitative approach based on library research was employed, utilizing descriptive-analytical methods and source triangulation from scientific journals, Central Bureau of Statistics publications, and government policy documents spanning 2021–2025. Findings reveal that palm oil, rubber, and rice are the three dominant commodities that substantially contribute to the Gross Regional Domestic Product (GRDP), employment absorption, and poverty alleviation. Nevertheless, reliance on raw commodity exports and insufficient downstream processing industries impede the region's structural economic transformation. Recommended development strategies encompass land intensification, adoption of smart agriculture technology incorporating Internet of Things (IoT) and Artificial Intelligence (AI), strengthening downstream processing through integrated agro-industrial zones, and institutional synergy among government, business actors, and farming communities. Commodity-based agricultural development is believed capable of driving inclusive, competitive, and globally resilient economic growth.